TO COMPARE THE OUTCOME AFTER USING LIGHTWEIGHT OR HEAVYWEIGHT MESH FOR THE REPAIR OF INGUINAL HERNIA (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Hernia repair is one of the most commonly performed procedures by general surgeons. With the introduction of tissue tension as an important factor, lichtenstein tension free mesh repair has become the standard procedure to be accepted worldwide.Objective : Comparative study Of Lightweight Or Heavyweight Mesh For The Repair Of Inguinal Hernia With Reference To Postoperative Pain, Short Term Recurrences, Seroma Formation And Foreign Body Sensation. Method :This study was conducted on 50 patients of inguinal hernia attending the surgical out-patient clinic of Smt. N.H.L. Municipal Medical College and associated Vadilal Sarabhai General Hospital, Ahmedabad from October 2017 to July 2019.Patients for the study were selected from amongst those attending the surgical OPD of the Vadilal Sarabhai Hospital with clinical diagnosis of inguinal hernia.All male patients 18 years and above diagnosed with inguinal hernia. Results:This study recorded a significant reduction of postoperative pain following Lichtenstein inguinal hernia repair with a lightweight mesh.  This study recorded more incidence of foreign body sensation in heavyweight mesh group, which is statistically significant. This study noted more incidence of seroma formation in heavyweight mesh group, but this is not statistically significant. No recurrence was reported in either group during the follow-up period of six months. Although follow-up period was short, there is a trend towards both meshes being equally effective.Conclusion : Finally it can be recommended from this study that use of Lightweight mesh in Lichtenstein hernia repair is a valid alternative to the Heavyweight mesh with reduced postoperative pain, foreign body sensation and seroma formation. The risk of hernia recurrence warrants longer follow-up period.
Keywords: Hernia; Lightweight Or Heavyweight Mesh; Postoperative Pain